THE USE OF PUNS TO GENERATE HUMOR IN DAD JOKES: A SCRIPT-BASED SEMANTIC THEORY OF HUMOR ANALYSIS - Dwi Khumaeroh Sa'adah,; Dewi Kustanti,; Ruminda, (Elite : English and Literature Journal, 2024)
Dad jokes have become a trend lately. Despite often being perceived as boring and unfunny, dad jokes are still practical in generating laughter. A critical component that makes dad jokes humorous is the use of puns. This research aims to classify the types of puns and how these puns generate humor in dad jokes. The data were the sentences that contained puns gathered from the @Dadsaysjokes X account. The research applied a qualitative method and presented a descriptive analysis. The semantic analysis of the data is supported by the puns classification theory developed by Delabastita (1996) and the Script-based Semantic Theory of Humor (SSTH) developed by Raskin (1985). The results of this research show that there are four types of puns in the dad jokes, which are homonymy, homophony, homography, and paronymy, that generate humor through ambiguity. In conclusion, dad jokes consist of puns that carry multiple meanings and amuse people through creative wordplay, so it breaks down the societal stigma that views dad jokes as boring and unfunny.